The Pedagogic and Professional Competencies of Arabic Language Teachers in The Public Islamic High School (MAN 1) Mojokerto - Noviya Ekasanti; Wildana Wargadinata; Nur Ila Ifawati (Prodi Bahasa Arab dan Lembaga Bahasa Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
Purpose - This research aims to explain the pedagogic competence of arabic teachers in the learning process and pedagogic competencies of Arabic teachers in learning evaluation. The objects in this study were all Arabic teachers at MAN 1 Mojokerto consists of 4 teachers. Design/methodology/approach - A qualitative approach with observation, interviews, documentation as complementary data. Findings - The research results obtained by researchers include, Most Arabic teachers make lesson plans globally for one year. They use learning methods according to the circumstances and abilities of students to achieve learning objectives; their classroom management abilities are related to the methods used. They do not use learning media due to the limitations of the school's media and the teacher's lack of ability to apply the latest media. Most of the Arabic teachers in Learning Evaluation use the test results as a tool to improve future exams and for selecting students until they can follow certain competencies Originality/value - The competence of Arabic language teachers, which is sometimes questioned, is not a problem in this study. This is because the teachers who teach Arabic at the research sites are state teachers, perhaps it is necessary to follow up more deeply on the competence of Arabic teachers in private schools. Paper type – Research paper